Noncompliance in AIDS Research - Arras, John D. (The Hastings Center report, 1990)
Participants in AIDS research may justify noncompliance with protocols by a “coercion defense.” While this defense may not be philosophically successful, a prudent social policy can enhance compliance by encouraging community participation and providing greater access to non-validated therapies.